Sustainable development through foster care: protecting abandoned children in Malaysia - Nadhilah A.Kadir,; Athirah Mohd Anuar, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Abandoned children in Malaysia often endure significant challenges, facing distressing situations, and tragically, some are even discovered in dire circumstances. Research indicates that institutional care can adversely impact their development, highlighting family-based care, particularly foster care, as a more favorable option. Despite the recognition of family-based care in the amendments to the Child Act 2001in 2016, challenges arise due to the absence of specific legislation and limited provisions on foster care in the Child Act 2001. This paper employs a qualitative approach, based on library research, to delve into foster care as a preferable alternative care for abandoned children from a legal standpoint. The study, in alignment with Goal 3 of the Sustainable Development Goals (SDGs) explores the crucial role of foster care in promoting the health and wellbeing of abandoned children. The research findings aim to contribute to the enhancement of child’s best interests and the fortification of the child protection system in Malaysia. By addressing challenges and filling gaps in the foster care system, the paper strives to foster an inclusive society that prioritizes the overall wellbeing of its children.